Hematotoxic ameliorative potential of hydromethanol extract of Justica secunda and astymin in 2, 4-dinitrophenylhydrazine-induced anemic male wistar rats - Samuel Kelechi Mobisson; Chiamaka Blossom Godson; Uchechukwu Loveth Iyanyi; Ben Enoluomen Ehigiator; Agona Odeh Obembe (Golestan University Of Medical Sciences, 2024)
Background: The number of people experiencing a type of anemia in Nigeria is on the rise. Hence, this study examines the comparative impact of Justicia secunda hydro-methanolic leaf extract and astymin on hematologic indices and antioxidant markers in phenylhydrazine (PHZ)-induced anemic male Wister rats. Methods: Twenty rats weighing between 90g and 170g were divided into five groups (A-E), with four rats in each group. The first group served as control; groups B to E received PHZ, PHZ + astymin (0.5mg/kg), PHZ + J. secunda (0.2mg/kg), and PHZ + J. secunda (0.5mg/kg), respectively. All animals in groups B to E received 2mg/kg PHZ intra-peritoneally for two days, and after that, administration of astymin and J. secunda commenced for 14 days using gavage. Results: The PCV, RBC, and HB significantly (p<0.01) increased in PHZ + J. secunda treated groups compared to the control. MCHC significantly decreased in PHZ + astymin compared to the control. Total WBC and neutrophil significantly reduced in groups administered with extract compared to control. Monocytes increased significantly in the treated groups compared to the control group. Eosinophils significantly increased in PHZ negative control compared to control. Urea and creatinine increased significantly in the treated groups compared to control. Total Bilirubin increased significantly in groups that received the extract compared to the control group. Conjugated bilirubin was increased significantly in PHZ control and PHZ + astymin compared to control. Total protein significantly increased in PHZ + J. secunda (0.5mg/kg) than control. Lymphocytes, platelets, MCV, MCHC, and albumin concentrations showed no statistically significant alternations.  Serum GSH and GPx significantly increased in treated groups compared to control. Catalase significantly (p<0.001) decreased in treated groups than control. Superoxide dismutase significantly increased in the PHZ + astymin group compared to the control group. MDA significantly decreased in the PHZ + astymin group compared to the control group. Conclusion: PHZ treatment caused toxicity of blood parameters and altered biochemical markers, while astymin and J. secunda treatment had ameliorative effects. Hence, J. secunda may provide benefits in managing anemia and oxidative stress if our findings are confirmed in human subjects.